The federative pact in the construction of the national education system: from the fulfillment of competences to the perspective of the guarantee of the right (Research, Society and Development, 2018)
Problems around distinctions in offer and educational quality in Brazil reflect disarticulation between educational systems and difficulties in management conditions. The alternative to overcome the challenges to effect this social right would be the construction of the National System of Education (SNE), able to articulate and integrate educational systems, considering the complexity of the Brazilian federal system. Therefore, this qualitative research analyzed, with the perspective of dialectical historical materialism and through analysis of content, the organization logical of Health Unic System (SUS) and the Single Management of Basic Education of the State and Municipal Public Education Networks of Mato Grosso, with the purpose to comprehend the federal cooperation to construct SNE. Without exhausting this discussion, the found elements found reiterate the importance of interfederative relationships in making effective public politics, and the importance of the federal pact as a condition to materialize the right to education.